2012
DOI: 10.1007/s13197-012-0900-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sugar composition during baking and their effects on sensory attributes of baked sweet potatoes

Abstract: The objective of this study was to evaluate the influence of sugar composition on the sensory attributes of seven baked sweet potatoes. The sugar composition was analyzed using high performance liquid chromatography. Results showed that the total sugar content of baked sweet potatoes increased significantly because of the formation of maltose. The maltose content dramatically increased after baking, and became the major sugar component of baked sweet potatoes. On the other hand, baked sweet potatoes were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 26 publications
4
37
0
Order By: Relevance
“…Total sugar and nonreducing sugar content of muffins was significantly ( p < 0.05) increased while reducing sugar content was decreased as compared to WCF. The increase in total sugar content of muffins can be ascribed to maltose formation during baking process (Chan et al, ). However, high protein content of muffins (Table a) particularly due to egg incorporation favors the milliards reaction during baking which might have decreased the reducing sugar content in muffins.…”
Section: Resultsmentioning
confidence: 99%
“…Total sugar and nonreducing sugar content of muffins was significantly ( p < 0.05) increased while reducing sugar content was decreased as compared to WCF. The increase in total sugar content of muffins can be ascribed to maltose formation during baking process (Chan et al, ). However, high protein content of muffins (Table a) particularly due to egg incorporation favors the milliards reaction during baking which might have decreased the reducing sugar content in muffins.…”
Section: Resultsmentioning
confidence: 99%
“…The average reducing sugar content in fresh and roasted sweet potato was 10.29 and 26.17 g/100 g DW, respectively. These results indicated that sugar content increased significantly due to the degradation of starch and formation of maltose (Chan et al, ). Our results were similar to those reported by Van hal (), whose study showed that the reducing sugars in different sweet potato flours ranged from 1.2% to 24.4% DW.…”
Section: Resultsmentioning
confidence: 91%
“…Our results were similar to those reported by Van hal (), whose study showed that the reducing sugars in different sweet potato flours ranged from 1.2% to 24.4% DW. Chan et al () found that the correlation between overall acceptability of sensory evaluation and sweetness was higher; therefore, roasted sweet potatoes with higher sugar content are assumed to have better overall acceptability. In addition, the Maillard reaction between amino acids and reducing sugars results in food having a brown color and distinctive flavor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, sweetness, color, and flavor are correlated with both the degree of maillard reaction and the overall acceptability of final products. However, there is little information about the effect of roasting on the quality of roasted sweet potatoes (Lai, Huang, Chan, Lien, & Liao, 2013), and only the effects of sugar content on sensory evaluation have been reported (Chan et al., 2014). What's more, as far as we know, no study has been conducted to investigate the effects of roasting on the changes in volatile compounds and sensory qualities of sweet potatoes, especially for different cultivars.…”
Section: Introductionmentioning
confidence: 99%